Relationship between tonic inhibitory currents and phasic inhibitory activity in the spinal cord lamina II region of adult mice - Ataka Toyofumi; Gu Jianguo G (SAGE Publishing, 2006)
Abstract Phasic and tonic inhibitions are two types of inhibitory activities involved in inhibitory processing in the CNS. In the spinal cord dorsal horn, phasic inhibition is mediated by both GABAergic and glycinergic inhibitory postsynaptic currents. In contrast to phasic inhibitory currents, using patch-clamp recording technique on spinal cord slices prepared from adult mice we revealed that tonic inhibitory currents were mediated by GABAA receptors but not by glycine receptors in dorsal horn lamina II region. We found that there was a linear relationship (r = 0.85) between the amplitude of tonic inhibitory currents and the frequency of GABAergic inhibitory postsynaptic currents. Analysis of charge transfer showed that the charges carried by tonic inhibitory currents were about 6 times of charges carried by phasic inhibitory currents. The prominent charge transfer by tonic inhibitory currents and their synaptic activity dependency suggest a significant role of tonic inhibition in sensory processing.